2018
DOI: 10.1063/1.5006214
|View full text |Cite
|
Sign up to set email alerts
|

Generating one to four-wing hidden attractors in a novel 4D no-equilibrium chaotic system with extreme multistability

Abstract: By using a simple state feedback controller in a three-dimensional chaotic system, a novel 4D chaotic system is derived in this paper. The system state equations are composed of nine terms including only one constant term. Depending on the different values of the constant term, this new proposed system has a line of equilibrium points or no equilibrium points. Compared with other similar chaotic systems, the newly presented system owns more abundant and complicated dynamic properties. What interests us is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 69 publications
0
40
0
3
Order By: Relevance
“…Multistability refers to the phenomenon that the system shows different dynamic characteristics and different attractors coexist under same parameters [62]. In recent years, the study of multistability and coexistence attractors is a hot topic in nonlinear dynamics [63][64][65][66][67][68][69][70]. Lai et al [63] showed the coexistence behavior of different attractors under different initial conditions and parameter values, such as four limit cycles, and two double-scroll attractors with a limit cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multistability refers to the phenomenon that the system shows different dynamic characteristics and different attractors coexist under same parameters [62]. In recent years, the study of multistability and coexistence attractors is a hot topic in nonlinear dynamics [63][64][65][66][67][68][69][70]. Lai et al [63] showed the coexistence behavior of different attractors under different initial conditions and parameter values, such as four limit cycles, and two double-scroll attractors with a limit cycle.…”
Section: Introductionmentioning
confidence: 99%
“…is new system had no equilibrium point, but it could also show rich and complex hidden dynamics. Zhang et al [66] introduced a state variable into a 3D chaotic system and then analyzed the dynamic characteristics of the new system under different initial conditions, proving that the new system has extreme multistability. In fact, various systems exhibiting multistability have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (4) represents two circles of equilibrium points (x 2 + y 2 + x= 0 and x 2 + y 2 −x = 0) touching at the origin in the x-y plane as shown in Figure 1. The bifurcation analysis of a nonlinear dynamical system is useful for knowing the behavior of the system both chaotic or periodic behavior for certain values of the system parameters [18][19][20][21][22][23]. Lyapunov exponent spectrum and bifurcation diagram are obtained for b = 4.5, c = 1 as a varies between 4 to 15 and initial condition X(0) = (0.01, 0.02, 0.01).…”
Section: Dynamical Model Of the New Chaotic Systemmentioning
confidence: 99%
“…Other many hyperchaotic systems have come out of the Lorenz-like system [28][29][30][31]. Some other hyperchaotic ones have been proposed, including a memristive hyperchaotic system [32,33], fractional order hyperchaotic system [34,35] or hyperchaotic multi-wing system [36,37]. To the best of our knowledge, there is no relevant research on a hyperchaotic hidden attractor with geometric control.…”
Section: Introductionmentioning
confidence: 99%